Implementation of the Criminal Justice System for Employment in Indonesia - Wijaya, Dion Untung; Priyanto, Eka; Irawan, Feri; Kurniati, Yeti; RAS, Hernawati (PT FORMOSA CENDEKIA GLOBAL, 2024)
This study explores the effectiveness of the implementation of the labor criminal justice system in Indonesia in providing fair and equitable legal protection for workers, and identifies the obstacles and challenges faced in the process of enforcing labor law. Through qualitative descriptive methods, data were collected from in-depth interviews with various stakeholders and analysis of related documents. The results of the study indicate that limited human resources and budget, corrupt and nepotistic practices, lack of legal understanding, and uneven distribution of labor courts are the main obstacles in enforcing labor law. To overcome these obstacles, strategies are needed that include increasing capacity and budget, strengthening supervision and accountability, legal counseling, and increasing access to labor courts. With the implementation of these strategies, it is hoped that the labor criminal justice system in Indonesia can run more effectively, fairly, and provide maximum protection for workers